Upaya Edukatif-Pedagogis Tentang Signifikansi Pendidikan Kecerdasan Moral Bagi Anak Usia Dini di Dusun Meramun - Rezeki Putra Gulo; Sisi Sisi; Yanuar Ada Zega (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Community Service (PKM) was held in Meramun Hamlet, Janjang Village, Tayan Hulu District, Sanggau Regency, West Kalimantan. The methods used by the service team are field observation and library research. The implementation of this PKM aims to offer ideas on the problems found by the PKM service team at the place where the activity was carried out, namely: Some early childhood children in the Meramun hamlet have begun to experience moral degradation, such as not respecting their parents, swearing at them, and not having good manners when communicating. So as a contribution of thought from the PKM service team, namely, providing educative-pedagogical education to early childhood in the Meramun hamlet about eight important points of moral intelligence that they must know and apply, namely: Empathy, conscience, self-control, love, respect , tolerance, fairness, and courtesy. The final conclusion of the PKM service team is that moral intelligence is one of the main indicators that is able to form generations of noble character and fear of God.